Preparation and cyclic oxidation resistance of Hf-doped NiAl coating. (February 2022) - Zhang, W.L.; Li, S.M.; Fu, L.B.; Li, W.; Sun, J.; Wang, T.G.; Jiang, S.M.; Gong, J.; Sun, C.
Abstract: NiAl coating, 5Hf-NiAl coating and 15Hf-NiAl coating were prepared on Ni-based superalloy by electroplating, arc ion plating (AIP) and subsequent vacuum annealing. Cyclic oxidation behavior of the three coatings was investigated at 1100 ℃. 5Hf-NiAl coating and 15f-NiAl coating exhibited excellent adhesion between thermally growth oxide (TGO) and coating. The uniformly dispersed Hf-rich precipitates contributed to the cyclic oxidation resistance. The oxidation mechanism and effect of Hf on the morphologies, rumpling and adhesion of TGO were discussed as well. Highlights: Hf-doped NiAl coating was prepared by electroplating and arc ion plating. Hf-rich precipitates was uniformly dispersed through the outer β-NiAl zone. Doping Hf in the coating had advantageous effects on the morphologies of TGO. Adding Hf was beneficial to reduce the degree of rumpling of TGO. Doping Hf in the coating enhanced the adhesion of TGO.